Temperature dependences of surface magnetoelastic constants of ultrathin Fe/GaAs (001) films - Żuberek, R.; Nesteruk, K.; Fronc, K.; Piechota, S.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The magnetoelastic constants of epitaxial iron films prepared by dc magnetron sputtering on single crystalGaAs (001) substrate in argon atmosphere and covered with a protective Si layer have been investigated in the temperature range 10–300 K by means of the strain modulated ferromagnetic resonance. It has been shown that the magnetoelastic constants strongly depend on the thickness of the film. The surface components of themagnetoelastic constants have been determined and analyzed within the Néel and dipolar models. The proposed analysis of experimental data gives chance for deeper insight into mechanisms responsible for magnetostriction of iron thin films.